Maximizing the Arabic Language Curriculum to Produce Graduate Qualifications at Integrated Islamic School - Ritonga, Apri Wardana; Ayu Desrani; Hamdani Ritonga (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
The qualifications of graduates learning Arabic can be measured by the quality of the curriculum applied. A certified curriculum is qualified when it passes the management process well. The study aims to analyze the management of the Arabic curriculum to produce qualified graduate qualifications. The author uses a descriptive qualitative approach through case study methods at As-Syifa Subang High School. The data was collected through observation phases and interviews with the Deputy Head of the Curriculum School. The results of this study revealed that As-Syifa Subang High School adopted the Merdeka Curriculum with a shared merdeka pattern. The management of the curriculum implementation is carried out after the concepts are well formulated. A variety of curricula include project based-learning, Al-Qur’an deepening, multilingual learning, character education, and entrepreneurship that are integrated into each subject. The findings of this study suggest that in addition to curriculum design there are important bodies that can produce qualified graduate qualifications, that is individual “learners” through good management support and educational materials that are accessible from a variety of sources.